U-type mechanical clamping to anchor the CFRP composites in strengthening of RC beams subjected to bending. (9th April 2021) - Letcham, K; Vincent, P
The present study investigates the performance of U-type clamp anchorage on external strengthening of reinforced concrete beams using carbon fibre-reinforced polymer composites. Unidirectional carbon fibre was used to strengthen the beam having a cross-section of 150 × 200 mm 2 and the fabricated U-type clamp was used as a clamping device to enhance the fibre-reinforced polymer (FRP) bonding. To test the beam, four-point bending system was adopted and the experimental parameters were the number of FRP layers. The failure mode of strengthened beams with U-type clamp was very similar (rupture of FRP composites) to the beams without U-type clamp. However, the delamination of FRP was evaded by counteracting the peeling stress development at the edge of fibre. Since the beams strengthened with U-type clamp exhibited more linear behaviour than that of the beams strengthened without U-type clamp, there may be a higher possibility for abrupt/rapid/brittle mode of failure and the ductility index of the beam with U-type clamp confirmed the above behaviour. However, the introduction of U-type clamp enhanced the flexural stiffness and ultimate strength by counteracting the debonding, and the beam with U-type clamp exhibited a maximum of 58.33% and 20.37% enhancement in flexural stiffness and ultimate strength than that of the beam without U-type clamp, respectively. The theoretical strength value of all strengthened beams was evaluated using models proposed in the previous research and compared with experimental results. It is inferred that the use of U-type clamp in FRP strengthening provides economic and structural benefits compared to a beam without U-type clamp.